PENGARUH PEMBERIAN AUDIOVISUAL ANTENATAL CARE EDUCATION TERHADAP TINGKAT KECEMASAN IBU PRIMIGRAVIDA UNTUK MENGHADAPI PERSALINAN - Mentari, Kadek Ratih (Coping: Community of Publishing in Nursing, 2014)
Antenatal care is an observation program, education and medical treatment in mother during the pregnancy. The use of the media in the disseminating information is to be expected to arise the will of primigravida’s psychological effect before labor. The aim of this study is to determine the effect of antenatal education through audiovisual media on the level of anxiety in third trimester of primigravida facing labor in Health Care Center South Denpasar Second Work Area . This research is a quasy-experimental study (pre-test and post-test with control group design). The Sample consisted of 30 pregnant women that was selected with purposive sampling. The measurement of anxiety levels was conducted by using the questionnaire Hamilton Anxiety Rating Scale (HARS) that would be conducted before and after the administration of standard education for 15 control groups and 13 min education through audiovisual media for 15 intervention groupss. The results of the study differences in changes in the level of anxiety in the control group and the intervention group using Man Whitney test was that you are z values ??obtained at -0.268 and Asymp.Sig value. (2-tailed) of 0.789 which has a greater value than ? studies (0,05), which means there is no change diffrent of anxiety level between control and intervention group
Keywords: Audiovisual Education, primigravida in third trimester; Antenatal Care; Anxiety levels of primigravida